Association between Sleep Duration and Hypertension among Adults in Southwest China. Issue 1 (21st February 2022) - He, Jie; He, Quan
Objective: This study aimed to evaluate the association between sleep duration and hypertension among adults in southwest China. Methods: Baseline variables were collected from a representative sample of 20, 053 adults aged 23–98 years in southwest China who received physical examinations from January 2019 to December 2020. All participants were categorized into either a hypertension group or a non-hypertension group. Sleep duration was classified as short (<6 h/day), normal (6–8 h/day), or long (>8 h/day). Baseline variables were compared between individuals with and without hypertension by rank-sum tests for two independent samples or χ 2 tests for nonparametric data. Multivariate logistic regression analysis was performed to evaluate the association between sleep duration and hypertension. Results: The overall incidence of hypertension was 51.2%. Unadjusted analysis showed that the risk of hypertension was higher in individuals with short (<6h/day) or long (>8h/day) sleep durations compared with those with a normal (6–8 h/day) sleep duration. The risk of hypertension was significantly increased by 30.1% in participants with a long (>8h/day) sleep duration compared with those with a normal (6–8h/day) sleep duration (OR = 1.301, P < 0.010, 95%CI = 1.149–1.475). The risk of hypertension was also increased by 1.1% in participants with a short (<6h/day) sleep duration compared with participants with a normal (6–8h/day) sleep duration, but the difference was not significant (OR = 1.011, P = 0.849, 95%CI = 0.905–1.129). After fully adjusting for confounding factors (model 4), the risk of hypertension was increased significantly (by 25%) in individuals with a short (<6h/day) sleep duration (OR = 1.25, P = 0.02, 95%CI = 1.036–1.508) but not in those with a long (>8h/day) sleep duration (17.5% increase) compared with participants with a normal (6–8h/day) sleep duration (OR = 1.175, P = 0.144, 95%CI = 0.946–1.460). Conclusion: The results of this study indicate that a short (<6h/day) sleep duration is related to an increased risk of hypertension, suggesting that sleep helps to protect against hypertension.